Beyond TEI: Returning the Text to the Reader - Christian Wittern (Journal of the Text Encoding Initiative)
Much research and effort has been invested in creating a versatile format for digital texts and the TEI is now widely used in many communities. Much less consolidated thought has been spend to publish and distribute digital texts in ways that are most useful to scholars. To remedy this situation, this paper proposes new, additional publication forms for digital texts through distributed version control systems. This will allow publication and maintainence of several different versions of a text. In some respects, this will be similar to publishing a college or paperback edition of the text established in a critical edition. In addition to this, the user of a text published through such a system can subscribe to later changes or corrections of an edition. The architectural model proposed in this paper tries to contribute to a fundamental protocol that could form the base for applications serving the long-term needs of research and scholarship.